ANALISIS STABILITAS PADA PROYEK PASANGAN BRONJONG UNTUK TANGGUL PANTAI DI AREA PERMUKIMAN KENJERAN - Arik Triarso; Bagus Dwipurwanto (Fakultas Teknik, Universitas Wiraraja, 2021)
This gabion embankment project is needed to reduce seawater erosion on residential roads in Kenjeran. This embankment has a height of up to 4 m. The main material of the embankment is using galvanized wire gabions with a size of 1 x 2 / 0.5 m. The soil data shows that the bottom soil of the embankment and embankment is sandy silty loam. The modeling was done using Plaxis 2D software and manual calculation of embankment stability. The results of the analysis show that the stability against rolling = 8.7; Stability to shear = 1.52; Global stability = 1.57; Stability of bearing capacity with SF creek reinforcement > 3. From this analysis, it can be concluded that the stability of the embankment in the category is safe.